Linked simulation for fire-exposed elements using CFD and thermo-mechanical models. (May 2019) - Šulc, Stanislav; Šmilauer, Vit; Patzák, Bořek; Cábová, Kamila; Wald, František
Highlights: A new API approach for simulation of muli-physical problem. Linking computational fluid dynamics, thermal and mechanical analysis. Elaborated concept of Adiabatic Surface Temperature. Validations on timber and concrete members exposed to fire. Abstract: Structural fire assessment belongs essentially to the design of steel, concrete or timber structures. The article presents a weakly-linked computational approach, employing the concept of adiabatic surface temperature (AST). The simulation comprises computational fluid dynamics (CFD), heat transport and solid mechanics. Application programming interfaces in linked codes (FDS, OOFEM) define methods for steering, data storage, visualization or fields mapping. The linked simulation is successfully validated on timber and concrete structural elements exposed to fire.